Large scale experimental trial of 5G mobile communication systems - TDD massive MIMO with linear and non-linear precoding schemes - Wang, Xin; Tian, Tingjian; Kashima, Tsuyoshi; Hou, Xiaolin; Jiang, Huiling; Benjebbour, Anass; Saito, Yuya; Kishiyama, Yoshihisa; Qiu, Jing; Shen, Haihua; Tang, Chen (2016 IEEE 27th Annual International Symposium on Personal, Indoor, and Mobile Radio Communications (PIMRC), 2016)
Recently, NTT DOCOMO and Huawei conducted a large-scale experimental trial of key technologies for the 5th generation (5G) mobile systems. Downlink multi-user (MU) transmission with massive MIMO in the time-division duplex (TDD) mode is one of the technologies evaluated in this trial. With linear and non-linear downlink precoding schemes, we investigated the practical performance of MU massive MIMO systems under different numbers of users, user distributions, and different radio frequency channel calibration settings with up to 24 users deployed. When linear precoding is used, the cell spectrum efficiency reaches 39 bit/s/Hz, and it reaches 43 bit/s/Hz when non-linear precoding is used. In term of the cell throughput, up to 1.35 Gbps cell throughput was observed with a linear precoder and 100 MHz bandwidth; and 343 Mbps cell throughput was observed with a non-linear precoder and 20 MHz bandwidth. Based on these investigations, we verified the feasibility and performance of a TDD massive MIMO system for 5G mobile systems, and studied the impact of key factors on the system performance.